Paradigma Hukum: Perspektif Filsafat Ilmu Rene Descartes, Auguste Comte, Thomas S Kuhn - Max Boli Sabon (Universitas Katolik Indonesia Atma Jaya Jakarta, 2016)
Rene Descates, August Comte and Thomas Kuhn are the three pioneers of philosophy science during their carreers. Rene Descartes is known as “the father of the modern philosophy” regarding his “cogito ergo sum” theory, which successfully attracted huge attention in cosmic and teology world.. Auguste Comte and his “law of three stages” theory that once shaked the philosophy world during the positivism period. His theory and thoughts have been great inspiration until recently. However, his theory about the truth was neglected by Thomas Kuhn with his new theory which is known as “the structure of scientific revolution”. Thomas Kuhn saidd :”Those scientists despite their knowledge could not solve the meaning of the truth, but only solving the puzzle pieces”. This theory surely lead to reactions from many parties. According to those scientists, the development in philosophy science is a development in every fields, whereas including law science. Through the library studies method and analogy method, we could find out that eventhough those scientists came from different eras, and produced different theories and opinions, the result of it is in fact they have similar views: “ Science is not just limited to science only, but also includes law science dedicated to humans and the communities in their daily life. This true fact about law science is the real paradigm that still is debatable”.